Intensitas Kerusakan Tanaman Cengkeh (Syzygium aromaticum L.) Akibat Serangan Hama dan Penyakit di Negeri Hitu Lama, Kecamatan Leihitu Kabupaten Maluku Tengah - Luanmasa, Santy P; Leatemia, J Audrey; Uruilal, Costanza (Universitas Pattimura, 2023)
This study aims to determine the main pests and diseases of tuni and forest clove and to get data of the damage intensity caused by them in clove plantation (“dusung”) in Hitu Lama village, Leihitu District, Central Maluku Regency. The method used is a survey method in four dusung of each tuni clove and forest clove. The observation of plant damage was done on 10% of plants in each dusung. The results showed that the main pest on tuni clove is stem borer (Nothopeus sp.) while on forest clove is a leaf eater. The main diseases found on both cloves plants is leaf spot disease (Cylindrocladium quinguseptatum and Pestalotia palmarum). The damage intensity of stem borer on tuni clove was 31.76% (moderate category) and leaf eaters on forest clove was 12.11% (mild category). The intensity of damage due to leaf spot disease on tuni and forest cloves was 23.39% and 20.76% respectively, both are mild category.